1986
DOI: 10.1029/pa001i002p00163
|View full text |Cite
|
Sign up to set email alerts
|

Pliocene‐Pleistocene evolution of the North Pacific Ocean‐Atmosphere system, interpreted from fossil diatoms

Abstract: The relative abundance of diatom taxa in 216 core tops has been quantified and compared, using cluster analysis, with assemblages in six cores located beneath different water masses of the North Pacific Ocean. All but one sequence span at least 1.5 m.y., (early Pleistocene to Holocene), and one extends to 2.6 Ma. The quantitative abundance of each taxon and the space‐time occurrence of each cluster are interpreted as tracers of oceanographic conditions. In addition to high‐frequency (glacial‐interglacial) osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 31 publications
5
87
0
Order By: Relevance
“…Although insolation at 65°N peaks during MIS 25, circa 0.94 Ma [Berger and Loutre, 1991] because of high eccentricity, the rising limb of %C 37:4 occurs during the previous eccentricity peak, suggesting that North Pacific water mass distribution is not controlled by insolation. At present, the distinctive salinity maximum of the subarctic gyre is linked to the excess precipitation that results from the strong Aleutian low-pressure system and the resulting winter storms and reduced cloud cover [Sancetta and Silvestri, 1986]. A weaker East Asian winter monsoon between MIS 22-16 is consistent with weaker Aleutian low-pressure and Siberian high-pressure systems [Heslop et al, 2002], but occurs after the decline in %C 37:4 and thus cannot be considered as a forcing mechanism.…”
Section: Position Of the Arctic Front During The Mptmentioning
confidence: 85%
See 4 more Smart Citations
“…Although insolation at 65°N peaks during MIS 25, circa 0.94 Ma [Berger and Loutre, 1991] because of high eccentricity, the rising limb of %C 37:4 occurs during the previous eccentricity peak, suggesting that North Pacific water mass distribution is not controlled by insolation. At present, the distinctive salinity maximum of the subarctic gyre is linked to the excess precipitation that results from the strong Aleutian low-pressure system and the resulting winter storms and reduced cloud cover [Sancetta and Silvestri, 1986]. A weaker East Asian winter monsoon between MIS 22-16 is consistent with weaker Aleutian low-pressure and Siberian high-pressure systems [Heslop et al, 2002], but occurs after the decline in %C 37:4 and thus cannot be considered as a forcing mechanism.…”
Section: Position Of the Arctic Front During The Mptmentioning
confidence: 85%
“…However, the complex extratropical response to ENSO variability within our present climate system limits acceptance of this mechanism. Analysis of diatom assemblages across the North Pacific has shown that between 1.0 and 0.8 Ma, in parallel with the reduction in %C 37:4 shown in Figure 3, the western Pacific experienced enhanced climate variability [Sancetta and Silvestri, 1986]. This variability included periodic migrations of the Subarctic Front over several degrees of latitude and an enhanced variability in the subarctic Pacific between intervals of stronger and weaker seasonal contrasts [Sancetta and Silvestri, 1986].…”
Section: Position Of the Arctic Front During The Mptmentioning
confidence: 99%
See 3 more Smart Citations